Applied Grant Writing Training for Future Health Communication Researchers: The Health Communication Scholars Program. Issue 2 (1st February 2017) - Mackert, Michael; Donovan, Erin E.; Bernhardt, Jay M.
ABSTRACT: Health communication faculty face increasing expectations regarding their academic productivity, including the expectation to seek and secure external funding. Doctoral training in health communication that does not fully prepare students for the challenges of securing external funding is doing them a disservice that will make them less competitive for academic positions and less likely to succeed in the academic positions they assume. The purpose of this study is to share the evaluation of a program, the Health Communication Scholars Program (HCSP), designed to train future health communication researchers in the pursuit of external funding. The HCSP includes a grant-writing workshop, requires interdisciplinary graduate student teams to submit applications, and awards funding to top proposals. HCSP participants responding to an evaluation survey ( N  = 25) had overwhelmingly positive experiences; respondents felt the program provided great value, improved their writing skills, gave them skills to pursue funding in the future, and helped them secure tenure-track faculty positions. The results of this formal evaluation suggest the HCSP is an experience that builds crucial skills and prepares graduate students for the demands they will face as faculty. It is a relatively low-cost, replicable model that merits consideration and adoption at other institutions that hope to provide professional development for doctoral students interested in health communication.